2021
DOI: 10.1038/s41598-021-90674-w
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between non-small cell lung cancer and radiation pneumonitis after carbon-ion radiotherapy by 18F-FDG PET/CT texture analysis

Abstract: The differentiation of non-small cell lung cancer (NSCLC) and radiation pneumonitis (RP) is critically essential for selecting optimal clinical therapeutic strategies to manage post carbon-ion radiotherapy (CIRT) in patients with NSCLC. The aim of this study was to assess the ability of 18F-FDG PET/CT metabolic parameters and its textural image features to differentiate NSCLC from RP after CIRT to develop a differential diagnosis of malignancy and benign lesion. We retrospectively analyzed 18F-FDG PET/CT image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…PET radiomics in pulmonary oncology gathered 107 articles [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ,…”
Section: Resultsunclassified
“…PET radiomics in pulmonary oncology gathered 107 articles [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ,…”
Section: Resultsunclassified
“…Differentiating radiation pneumonitis from residual/recurrent disease to avoid delay in treatment is a challenging issue after RT [37]. These may have a similar appearance on CT [38][39][40].…”
Section: Differential Diagnosis Toxicity Vs Tumor Progressionmentioning
confidence: 99%
“…Also, increased metabolism due to inflammation is common in ( 18 F)-FDG PET/CT images [40,41], which may decrease the accuracy of SUVs. To distinguish these two entities, Suga et al showed that two conventional radiomics features outperformed SUV (AUC = 0.83-0.82 vs. 0.63-0.64) but not MTV (AUC = 0.86) [37].…”
Section: Differential Diagnosis Toxicity Vs Tumor Progressionmentioning
confidence: 99%